1998
DOI: 10.1088/0022-3727/31/19/030
|View full text |Cite
|
Sign up to set email alerts
|

Combination of emission spectroscopy and fast imagery to characterize high-voltage circuit breakers

Abstract: To investigate the break phenomenon in high-voltage circuit breakers, a novel experimental approach combining spectroscopy and imagery for measuring electron density, temperature and arc geometry is presented. Images of the arc were taken using a narrow band optical filter, and spectra of the entire arc and in the same spectral region were recorded simultaneously. We report tests both on this method and on the available literature data and the results obtained on two different circuit breaker models. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Here, we use the w value given by Hartinger et al [4] and follow the standard procedure suggested by Olivero and Longbothum [8]. Fig.…”
Section: B Electron Densitymentioning
confidence: 99%
“…Here, we use the w value given by Hartinger et al [4] and follow the standard procedure suggested by Olivero and Longbothum [8]. Fig.…”
Section: B Electron Densitymentioning
confidence: 99%
“…As an in-direct measurement method, analysis of arc emission spectroscopy could determine the arc voltage and the dissipated arc energy between the contacts by considering transport properties of arc as air thermal plasma. Besides, Optical Emission Spectroscopy (OES) could provide detailed information on the arc composition by the emitted spectra of excited particles injected into the arc column [9][10][11]. Metal vapors in the arc could significantly change the arc properties like temperature and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[3]). This is because atomic and ionic species dominate in the high temperature regions and generate an intense spectral line radiation which can be well used for the determination of temperatures and species densities [6][7][8]. However, the analysis of low-temperature regions of the arc fringes, of the regions near nozzle walls and of the temporal phase of arc quenching is much more challenging due to low line radiation intensities.…”
Section: Introductionmentioning
confidence: 99%